Analisis Dampak E-Commerce Terhadap Pengaruh Penjualan UMKM - Riana Raharti; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the impact of E-commerce on the influence of MSME sales. The method used is Library Research (Library) in this writing, this method uses books, and journals, both written and online. Based on the results of this research, it can be concluded that E-commerce has a positive impact on MSMEs, including access to larger markets, reduced operational costs, marketing capabilities, in-depth data analysis, and brand development. E-commerce helps MSMEs to develop, increase efficiency, and build customer trust. In facing competition, MSMES needs to focus on effective marketing strategies and maintaining product and service quality. E- commerce is a powerful tool for the growth of MSMEs in the digital era.